Relocating the back office. (Economist, 2003)
The debate over "offshoring" has been brewing since a study by Forrester, a research group, in 2002 claimed that 3.3m white-collar American jobs (500,000 of them in IT) would shift offshore to countries such as India by 2015. Stephen Roach, the chief economist at Morgan Stanley, talks about a "new and powerful global labour arbitrage" that has led to an accelerating transfer of high-wage jobs to India and elsewhere. He reckons this is adding to the bias towards jobless recoveries in western economies. Multinationals may in future do original R&D in low-cost places, but for the moment most of the jobs on the move are the paper-based back-office ones that can be digitalised and telecommunicated anywhere around the world, plus more routine telephone inquiries that are increasingly being bundled together into call centres. The offshoring business remains predominantly English-speaking. It is dominated by American and British companies outsourcing their internal operations to third parties in places such as Ireland, Canada and South Africa, but most of all in India. The main advantage of shifting business operations to India and similar low-cost countries comes from a combination of lower wages and the improvement in the quality and price of international telecommunications. But the benefits of offshoring are not confined to lower costs. For one thing, offshoring allows companies to work round-the-clock shifts, ferrying data back and forth from one place to another as the sun sets. For another, it allows them to rethink the way they solve IT problems.